CONFIRMATORY FACTOR ANALYSIS ON THE LEGAL ASPECTS OF BUSINESS FUNDING WITH SECURITIES CROWDFUNDING SCHEME ON SMEs IN MEDAN MUNICIPAL CITY - M.Y.F. Hafidz Nasution; M. Pintor Nasution; Pardomuan Gultom (RADJA PUBLIKA, 2022)
SMEs is one of the important pillars in the national economic development who to date, are still faced with its classical issue in obtaining additional capital funding. The securities crowdfunding concept that was introduced to be the solution for SMEs is yet to reach the 64,2 million SMEs in Indonesia due to SMEs’ difficulties in complying to the regulatory requirements. Therefore, the objective of this research is to analyze the legal factors that may affect SMEs’ interests in obtaining capital funding via the securities crowdfunding concept. This research is conducted by using quantitative approach and analyzed by using the confirmatory factor analysis and descriptive analysis methods based on the primary data collected from 50 SMEs in BPC HIPMI Medan on a purposive sampling basis. Based on the research findings, the implementation of the disclosure principle in POJK 57/2020 are mainly the cause of SMEs’ inability and affecting interests in the securities crowdfunding concept. Therefore, further development of POJK 57/2020 as the regulatory basis of the securities crowdfunding concept are essential in supporting SMEs’ exponential growth in the future.